Analisis Pemahaman dan Kesadaran Hukum Bagi Pelaku Penyalahgunaan Narkotika di Panti Rehabilitasi Sibolangit Centre - Setri Cahyani; Laura Margaretha Br Pandia; Elan Valensi Gea; Sigar P. Berutu (Jurnal Hukum Lex Generalis, 2024)
Narcotics abuse is a serious global problem that is currently faced by many nations in the world. Because the interest or presentation of its use always never stops completely. This phenomenon is like an iceberg, only a small part of the surface is visible and most of it is invisible. For example, it is estimated that there are 100 narcotics abusers but only 1 person has been identified as the abuser. This narcotics problem is so disturbing and worrying because various kinds of damage and crime will emerge from it. At the Sibolangit Center Rehabilitation Home, understanding of the law for narcotics abuse for narcotics users in general is very low, which causes many people to use prohibited narcotics because there is little information available. Likewise, the results of the survey questionnaire prove that the average of 45 respondents answered that almost no never or rarely received information about the dangers of narcotics use. However, legal awareness of narcotics abusers who are in rehabilitation centers regarding the impact of criminal narcotics sentences in Indonesia tends to develop along with the rehabilitation process that has been undertaken, because narcotics users in rehabilitation are given an understanding of the dangers of narcotics abuse both in terms of health and the applicable law.